Short term effects of rapid maxillary expansion on breathing function assessed with spirometry: A case-control study - Andrea Abate; Davide Cavagnetto; Andrea Fama; Marco Matarese; Danilo Lucarelli; Fausto Assandri (Elsevier, 2021)
Background: The aim of this work is to evaluate changes following rapid maxillary expansion (RME) on breathing function in two groups of patients: mouth breathers and nasal breathers. Materials and methods: Twenty-five oral breather patients (12 male, 13 female, mean age 15.2 ± 1.3), and 25 nasal breather patients (14 male, 11 female, mean age 15.3 ± 1.6) were treated with RME. Breathing function was evaluated by computerized spirometry. Forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), Tiffenau index (FEV1/ FVC ratio, IT%), forced expiratory flow at 25-75% of vital capacity (FEF 25-75%), and Tidal volume (TV) were assessed. Breathing function analysis was performed before RME and 6 and 12 months after RME during follow-up appointments. The Shapiro-Wilk test was used to assess whether data were normally distributed. As data were not normally distributed, Mann-Whitney U and Friedman tests were used to perform comparisons between treatment groups and within group comparisons, respectively. Results: Oral breathers and nasal breathers showed statistically significant differences in FVC, FEF 25-75%, and TV at T0. They did not present any statistically significant difference in FEV1 and IT% at the same time point.Statistically significant differences were noticed for all indices in the oral breather group after maxillary expansion, while the nasal breather group showed statistically significant differences only in FCV, FEF 25-75%, and TV after treatment.There were no statistically significant differences in all indices 12 months after maxillary expansion between the oral breather and nasal breather groups. Conclusions: RME appeared to improve breathing function in both groups. Forced vital capacity (FVC), forced expiratory flow at 25-75% of vital capacity (FEF 25-75), and Tidal volume (TV) reached similar values in both groups after treatment with RME.